2023
DOI: 10.1007/s40964-022-00391-7
|View full text |Cite
|
Sign up to set email alerts
|

Vapour polishing of fused deposition modelling (FDM) parts: a critical review of different techniques, and subsequent surface finish and mechanical properties of the post-processed 3D-printed parts

Abstract: Fused deposition modelling (FDM), one of the most commonly used additive manufacturing techniques in the industry, involves layer-by-layer deposition of melted material to create a 3D structure. The staircase and beading effect caused by the printing process and temperature variation cause delamination and poor surface finish in FDM-printed parts. This hinders the use of these specimens in various applications, which are then usually resolved using pre-processing and post-processing techniques. Higher surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Figure 4 a shows that the lower layer thickness and higher infill density have lower Ra. Larger layer height results in a rougher surface finish because each layer is thicker, leading to a more noticeable stair-stepping effect [ 45 ]. With high infill density, a dense structure is formed with fine layers adhering to each other, thus reducing porosity and providing a smooth surface [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 a shows that the lower layer thickness and higher infill density have lower Ra. Larger layer height results in a rougher surface finish because each layer is thicker, leading to a more noticeable stair-stepping effect [ 45 ]. With high infill density, a dense structure is formed with fine layers adhering to each other, thus reducing porosity and providing a smooth surface [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review work, the most common post-processing treatments are cited for improving the surface roughness of parts manufactured in PLA by FFF/FDM. Among these treatments, the use of vapors or immersion in dichloromethane, chloroform or ethyl acetate, although it has been shown that the use of ethyl acetate is more advisable through either of the two techniques with the advantage of its reduced toxicity, availability and economical price (Lavecchia et al , 2022; Mathew et al , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…However, regardless of the method chosen, thorough cleaning of parts post-processing is crucial to remove any debris or residue. This step ensures the final surface quality meets the desired standards [25,38,40,41].…”
Section: B Sanding and Polishingmentioning
confidence: 99%